Analysis of Condition Monitoring for LRVP (Liquid Ring Vacuum Pump) Shaft Alignment Using Laser Alignment for Maintenance Actions at PT SEML - Fauzi, Arman; Abu, Risal; Mukhnizar, Mukhnizar (The Future of Education Journal, 2026)
The Liquid Ring Vacuum Pump (LRVP) is an important component in geothermal power plant systems that functions to extract non-condensable gases (NCG) such as H₂S, CO₂, and N₂ in order to maintain optimal condensation processes in the power generation system. One of the common problems occurring in pump systems is shaft misalignment, which can lead to increased vibration, temperature, and accelerated damage to components such as bearings and couplings. This study aims to analyze the alignment condition of the LRVP pump shaft using the laser alignment method as part of condition monitoring activities in the maintenance system at PT Supreme Energy Muara Laboh. The research method was carried out by measuring shaft alignment using a laser alignment device installed on the coupling between the motor, gearbox, and pump. The measurement data were then analyzed by comparing the alignment values with the tolerance limits specified by the equipment manufacturer. The results indicate that shaft misalignment can be caused by several factors such as installation errors, unstable foundations, operational vibrations, and inadequate maintenance of pump components. Misalignment that exceeds the tolerance limits may increase vibration and temperature, which can lead to damage to bearings and other mechanical components. Therefore, periodic monitoring and shaft alignment using the laser alignment method are essential to maintain pump performance and improve the operational reliability of geothermal power plant systems.